CO2 valorisation via Reverse Water-Gas Shift reaction using advanced Cs doped Fe-Cu/Al2O3 catalysts. (October 2017) - Pastor-Pérez, L.; Baibars, F.; Le Sache, E.; Arellano-García, H.; Gu, S.; Reina, T.R.
Highlights: Fe-Cu-Cs/Al2 O3 : advanced catalyst for CO2 conversion via RWGS. Cs is an excellent promoter to boost the activity/selectivity of FeOx based materials. Beneficial effect of Cu preventing Fe − active phase sintering. Suitability of these advanced catalysts for long term runs. Abstract: This paper evidences the viability of chemical recycling of CO2 via reverse water-gas shift reaction using advanced heterogeneous catalysts. In particular, we have developed a multicomponent Fe-Cu-Cs/Al2 O3 catalyst able to reach high levels of CO2 conversions and complete selectivity to CO at various reaction conditions (temperature and space velocities). In addition, to the excellent activity, the novel-Cs doped catalyst is fairly stable for continuous operation which suggests its viability for deeper studies in the reverse water-gas shift reaction. The catalytic activity and selectivity of this new material have been carefully compared to that of Fe/Al2 O3, Fe-Cu/Al2 O3 and Fe-Cs/Al2 O3 in order to understand each active component's contribution to the catalyst's performance. This comparison provides some clues to explain the superiority of the multicomponent Fe-Cu-Cs/Al2 O3 catalyst.